"There can be no racial improvisation in white supremacy": What we can learn when anti-racist pedagogy fails. Issue 1 (2nd January 2019) - Miller, Erin T.; Tanner, Samuel J.
Abstract: Using narrative research as a qualitative methodology, we (two white critical whiteness scholars) tell a story about how a dismantling and rebuilding of whiteness occurred in a fourth-grade classroom across three vignettes. Using a close read of Reverend Thandeka's primer on the ways white children are socialized, we wrestle with what pedagogy aimed to confront racism means when it didn't work as planned for a white child and his family. In our telling, we will attempt to wrestle with the question: What happens when white children are asked to engage in anti-racist pedagogy?